Tympanostomy Tube Complication in Otitis Media with Effusion - Rahim, Ghassan Hassan (AL-Kindy College Medical Journal, 2020)
Background: Otitis media with effusion is characterized by accumulation of fluid in the middle ear in absence of acute inflammation and  it is the most common cause of  acquired hearing loss in children, and may  negatively affect language development failure of medical treatment of middle ear effusion frequently require myringotomy and tympanostomy tube insertion.Objectives: To determine tympanostomy tube complications of tube in children with chronic otitis media with effusion who were treated with Shah Grommet tube insertion.Methods: The Medical records of 162 ears of 87 children (52 male and 35 female) were reviewed respectively, the patients ages were between 3 to 16 years old (mean age =8.11 years), patient were followed for 6-66 months (mean 23.3) after tympanostomy tube insertion. Tube extrusion time was also reviewed in all patients, and the indication for surgery was chronic middle ear effusion.Results: Otorrhea accured in nine ears (5.6%), granulation tissue was seen in 2 ears (1.2%), myringosclerosis in (34.6%) persistent perfor-ation (5.6%), atrophy (23.5%) retraction (16.7%) and medial displacement 1.2% the average extrusion time was 8.5 month ( ± 4.6).Conclusions: complications of tympanostomy tube insertion are common and the most common are otorrhea myringosclerosis, atrophy but they are generally insignificant consequently in majority of these complications there is no need for management.